Compound heterozygous TYK2 mutations underlie primary immunodeficiency with T-cell lymphopenia - Michiko Nemoto (Nature Portfolio, 2018)
Abstract Complete tyrosine kinase 2 (TYK2) deficiency has been previously described in patients with primary immunodeficiency diseases. The patients were infected with various pathogens, including mycobacteria and/or viruses, and one of the patients developed hyper-IgE syndrome. A detailed immunological investigation of these patients revealed impaired responses to type I IFN, IL-10, IL-12 and IL-23, which are associated with increased susceptibility to mycobacterial and/or viral infections. Herein, we report a recessive partial TYK2 deficiency in two siblings who presented with T-cell lymphopenia characterized by low naïve CD4+ T-cell counts and who developed Epstein-Barr virus (EBV)-associated B-cell lymphoma. Targeted exome-sequencing of the siblings’ genomes demonstrated that both patients carried novel compound heterozygous mutations (c.209_212delGCTT/c.691C > T, p.Cys70Serfs*21/p.Arg231Trp) in the TYK2. The TYK2 protein levels were reduced by 35% in the T cells of the patient. Unlike the response under complete TYK2 deficiency, the patient’s T cells responded normally to type I IFN, IL-6, IL-10 and IL-12, whereas the cells displayed an impaired response to IL-23. Furthermore, the level of STAT1 was low in the cells of the patient. These studies reveal a new clinical entity of a primary immunodeficiency with T-cell lymphopenia that is associated with compound heterozygous TYK2 mutations in the patients.